Unpaid and paid care: The effects of child care and elder care on the standard of living - Kijong Kim; Rania Antonopoulos (Levy Economics Institute of Bard College, 2011)
Transforming care for children and the elderly from a private to a public domain engenders a series of benefits to the economy that improve our standard of living. We assess the positive impacts of social care from both receivers' and providers' points of view. The benefits to care receivers are various, ranging from private, higher returns to education to enhancing subjective well-being and health outcomes. The economy-wide spillovers of the benefits are noteworthy. Early childhood education reduces costs of law enforcement and generates higher long-term economic growth. Home-based health care lowers absenteeism and job losses that otherwise undermine labor productivity, providing adequate care at a lower cost and delaying admission into high-cost institutional care. Social care improves mothers' labor-market attachment with higher lifetime income; it also lowers physical and psychological burdens of elder care that are becoming more prevalent with an aging population. Social care investment creates more job opportunities than other public spending, especially for workers from poor households and with low levels of educational attainment. The broad contributions of social care to our standard of living should be recognized in the public discourse, particularly in this era of fiscal austerity.
Keywords: J13; J14; J48; 330; child care; elder care; social care; quality of life